2022
DOI: 10.1002/jib.699
|View full text |Cite
|
Sign up to set email alerts
|

Transition metals in brewing and their role in wort and beer oxidative stability: a review

Abstract: Beer inevitably changes over time: the colour will darken, haze may form, and stale flavours develop, while others fade. The challenge of maintaining the fresh flavour quality of beer (over a typical 9-12 month storage period) is generally the determining factor of a beer's shelf-life for brewers, as opposed to colloidal or microbiological stability. Fortunately, as early as the brewhouse, oxidative degradation can -to a certain extent -be controlled, enabling the shelf-life to be increased. This review consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 309 publications
0
3
0
Order By: Relevance
“…Statistical analysis of the protein groups: (a) volcano plot constructed from Student’s t -test ( p > 0.05); (b) peroxidase label-free quantitation (LFQ) intensity in HW and UW treatments; (c) peroxidase structure extracted from the AlphaFold database. , *Difference (HW–UW) is between the LFQ abundance of the average of each treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analysis of the protein groups: (a) volcano plot constructed from Student’s t -test ( p > 0.05); (b) peroxidase label-free quantitation (LFQ) intensity in HW and UW treatments; (c) peroxidase structure extracted from the AlphaFold database. , *Difference (HW–UW) is between the LFQ abundance of the average of each treatment.…”
Section: Resultsmentioning
confidence: 99%
“…During the wort boiling, the protein thermally denatures, causing its unfolding and the exposing of the active sites containing the heme group as well as the hydrophobic sites and cysteine residues. The transition-metal ions are involved in several reactions to deplete the flavor stability in beer due to their capacity to form oxidative radicals . Within the compounds that are reactive to transition-metal ions, specifically ferrous iron stands the hop bitter acids .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of many of staling compounds are initiated by reactive oxygen species, which lead to chain reactions responsible for the formation of oxidation products such as carbonyl compounds (Vanderhaegen et al 2006;Baert et al 2012;Wietstock et al 2016) with 1-hydroxylethyl radicals reported as intermediates in the chain reactions (Andersen and Skibsted 1998;Elias et al 2009). The main pro-oxidants are transition metal ions, especially trace levels of iron and copper ions, which are the catalysts of oxidation via Fenton and Haber-Weiss reactions (Kaneda et al 1992;Vanderhaegen et al 2006;Mertens et al 2022). Overall, the rate of oxidative deterioration of beer is determined by the balance between the pro-oxidants and antioxidants.…”
Section: • Agata Soszka1mentioning
confidence: 99%
“…Flavour instability remains a challenge for the brewing industry (Bamforth 2011;Mertens et al 2022). From the sensory perspective during storage, beer flavour deteriorates (Zufall et al 2005).…”
Section: • Agata Soszka1mentioning
confidence: 99%